Other Tourists as Part of Tourism Product - Emiroglu, Begum Dilara (My University, 2021)
In the tourism services context, tourists receive services simultaneously with other tourists who consume services and\rshare the same service environment with them. Therefore, other tourists in the service environment may have a positive\rand negative impact on the tourist’s service experience due to some of their appropriate or inappropriate behaviours.\rThis may also affect the tourist’s subsequent purchasing behaviour. Hence, understanding the nature of tourist-tourist\rinteractions (T2T) is important for the tourism industry. However, there are very limited studies on this issue in the\rliterature. Therefore, this study was performed to explore incidents that cause satisfaction and disturbance of tourists\rduring interactions, how these interactions occur, what levels, and in which places. Therefore, semi-structured interviews\rwere conducted with 33 foreign tourists visiting Istanbul. In order to ensure the reliability and validity of the research,\rthe data triangulation technique was used, and a focus group interview was employed with seven tourist guides. The\rfindings revealed that the T2T interactions occurred directly and indirectly. Direct interactions consisted of spontaneous,\rsuperficial, and close interactions. Interactions occurred in service and public areas. Friendly, considerate, hostile,\rinconsiderate and rude, illegal and prohibited, offensive, and disgusting behaviours of other tourists caused the tourists’\rsatisfaction and disturbance.
Keywords: Otelcilik; Konaklama; Spor ve Turizm